Mass Transport Complex (Mtc) Control on the Basin Floor Stratigraphic Succession and Sand Deposition: An Observation from Deepwater Brunei - Herry Maulana; Harris Saifi Hakimi (Berita Sedimentologi, 2013)
Mass transport complexes (MTCs) are one of major geological features observed in many deepwater provinces, including in Deepwater Brunei, where MTCs are commonly initiated and deposited on the slope and basin floor settings. MTCs are broadly characterised on the basis of their internal characteristics and external morphological features. Posamentier (2004) offered a simple observational guideline for describing MTCs: 1) the underlying surfaces of MTCs usually are extensively scoured in a form of deep and linear grooves 2) the MTCs' overlying surface is mostly irregular - hummocky relief bounded laterally by gentle to steep flanks 3) MTCs often have transparent to chaotic seismic reflections, amalgamation of MTCs stacks is not uncommon, and 4) MTCs could have a morphology of channel or lobes.This guideline was utilised in describing the recent Brunei Mega MTCthough in much larger scale. This paper uses the same set of guideline to describe older MTCs observed in study area. We will also attempt to investigate MTCs' control on the overall basin floor stratigraphic succession and, in particular, sandstone deposition as it appears to be one of the key factors in delivering potential sands further into the basin floor.